Pengaruh Doping Zirkonium (Zr) pada Konstanta Dielektrik dan Struktur Kristal BaZrxTi1-xO3: Fildhaz Khairina Nisa, Anif Jamaluddin, Yofentina Iriani - Fildzah Khairina Nisa, Fildzah Khairina Nisa; Anif Jamaluddin, Anif Jamaluddin; Yofentina Iriani, Yofentina Iriani (Jurnal Fisika dan Aplikasinya, 2025)
Barium zirconium titanate (BaZrxTi1-xO3) with mole variations of zirconium (x) dopant at x = 0.01; x = 0.02; and x = 0.03 has been fabricated by solid state reaction method. Sintering temperature was done at temperature 11000 C with holding time for 2h. Sample was characterized with XRD instrument and RLC meter to determine the effects of doping on the crystal structures and dielectric constant of BaZrxTi1-xO3. The result of XRD analysis showed that BaZrxTi1-xO3 has a tetragonal structure with a = b = c. Crystalline size of BaZrxTi1-xO3 at x = 0.01; x = 0.02; and x = 0.03 are 34 nm, 33 nm, and 38 nm. RLC meter measurement obtained the dielectric constant are 331, 522, and 641, respectively.